Small Cell Lung Cancer with Positive Anti-Hu Antibodies Presenting as Gastroparesis - David N Moskovitz; Kenneth V Robb (Canadian Journal of Gastroenterology)
Lung cancer is the most common cancer in North America. Small cell lung cancer (SCLC) represents 15% to 25% of lung cancers. SCLC commonly relapses, resulting in a 3% to 8% five-year survival rate. The poor prognosis associated with SCLC is partly due to late diagnosis of the disease. Paraneoplastic syndromes can be early manifestations of SCLC. The potential benefit of early diagnosis has prompted investigations into markers of this disease. Some patients may present with predominantly gastrointestinal dysmotility symptoms that have no obvious explanation. Testing for anti-Hu antibodies, as a valuable marker of SCLC, should be considered in the investigation. A case of SCLC with positive anti-Hu antibodies presenting with intestinal pseudo-obstruction is presented. Gastrointestinal dysmotility as a manifestation of paraneoplastic syndrome is reviewed.